Changes in the understanding of competitiveness and the conditions for improving Hungarian competitiveness in the light of these changes - Csath, Magdolna (Public Finance Quarterly, 2024)
The aim of this article is to present the changes in the literature and practice of competitiveness, pointing out that a distinction must be made between competitiveness at the firm level and competitiveness at the national level, both in terms of objectives and methods. On the other hand, it highlights the new elements that have been introduced into the understanding of competitiveness due to geopolitical, social and environmental changes, and which are becoming more prominent in our time due to technological change. The article quotes, without claiming to be exhaustive, the main findings of recent studies by the best-known competitiveness research organisations, illustrating the differences in interpretation between them. Occasionally, findings on domestic performance are also discussed. The article did not aim to provide a comprehensive analysis of Hungarian competitiveness based on proprietary research, as it considers the presented MNB Competitiveness Report as a good research basis for describing the competitiveness situation and for developing a national competitiveness strategy. However, it does point out some additional indicators that should definitely be included in a national competitiveness strategy. It argues that the aim of improving national competitiveness should not be merely to improve economic outcomes, such as GDP. The central issue of improving competitiveness can only be the harmonious expansion of all elements of national wealth together. Therefore, the Hungarian National Competitiveness Strategy should set development targets for those elements of wealth where Hungarian competitiveness performance is weak. The article lists these in the summary.